THE STADY OF THE TRADITIONAL CULTURE OF THE ALTAIANS IN GORNY ALTAY WITHIN THE FRAMEWORK OF THE INTERNATIONAL ETHNOGRAPHIC EXPEDITION “BOLSHOI ALTAY” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article is based on ethnographic materials collected during the international research expedition “Great Altai” concerning the preservation of Altai traditional culture. Ethnographers from Russia, Kyrgyzstan and Uzbekistan conducted interviews and collected valuable materials on animal husbandry, material and intangible preserved traditional culture in Gornyi Altai.This study reflects the traditions, rituals, beliefs, and taboos of Altai people, especially their customs of hospitality and ceremony involving slaughtering cattle and serving meat to guests. It also reveals wedding and matchmaking traditions, including the preparation of Altai wedding dishes. Additionally, Altai and Kyrgyz traditions are analyzed and compared, noting the commonalities and features in their traditional cultures.
Keywords: ethnography, expedition, Altai, traditional culture, village, people, food, serving meat, guest, wedding.